Leksiko-sintaksičeskie izmenenija v sovremennom slovenskom jazyke - Žele, Andreja (Jezikoslovni zapiski, 2013)
In the multifunctional expansion of texts and the lexicon, it is especially due to the high degree of borrowing that the semantic-syntactic features of today's lexicon have also extended into the systemic character of Slovenian.
Keywords: besedotvorje; leksika; lexica; meaning creation; skladnja; Slovene; Slovene langauge; slovenščina; syntax; transformational generative capacity of Slovenian; tvorbeno-pretvorbene zmožnosti slovenščine; word formation